SLANT YÜZEYLER ÜZERİNE - AYKURT, SEZİN (Fırat Üniveristesi, 2011)
Bu çalışma dört bölümden oluşmaktadır.Birinci bölümde; Riemann ve kompleks manifoldlara dayalı bazı temel tanım ve teoremler verildi.İkinci bölümde; Slant alt manifold ve slant yüzey kavramları verilerek bazı slant yüzey örnekleri incelendi.Üçüncü bölümde slant manifoldlarda Gauss ve Codazzi denklemleri ele alınarak Varlık ve Teklik Teoremi verildi.Dördüncü bölümde ise H-Umbilik slant alt manifoldun tanımı ve Kaehlerian slant alt manifoldlarda skalar ikinci eğrilik ve ortalama eğrilik arasında teorem ve sonuç verildi.Anahtar Kelimeler: Hemen Hemen Kompleks Manifold, Kompleks Manifold, Slant Yüzey, H-Umbilik Slant Alt Manifold.

This thesis consists of four chapters.In the first chapter; some fundemental definitions and theorems are given with regard to Riemannian manifold and complex manifold.In the second chapter; some examples of slant surfaces are examined by giving the concepts of slant submanifold and slant surface.In the third chapter; existance and uniqueness are given by considering Gauss and Codazzi equations.In the fourth chapter; the definition of H-Umbilik slant submanifold is given. Also, theorem and corollary for inequality between scalar second curvature and mean curvature are given.Keywords: Almost Complex Manifold, Complex Manifold, Slant Surface, H-Umbilical Slant Submanifold.
On slant surfaces
Keywords: Matematik